2009
DOI: 10.1038/nn.2343
|View full text |Cite
|
Sign up to set email alerts
|

Disparity- and velocity-based signals for three-dimensional motion perception in human MT+

Abstract: How does the primate visual system encode three-dimensional motion? The macaque middle temporal area (MT) and the human MT complex (MT+) have well-established sensitivity to two-dimensional frontoparallel motion and static disparity. However, evidence for sensitivity to three-dimensional motion has remained elusive. We found that human MT+ encodes two binocular cues to three-dimensional motion: changing disparities over time and interocular comparisons of retinal velocities. By varying important properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
111
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 48 publications
8
111
2
Order By: Relevance
“…Importantly, these connections were statistically significant for all the disparity pedestals and are therefore probably independent of the specific disparity values used in our experiment. Recent fMRI studies have demonstrated that both areas hMTϩ and V3A are highly responsive to various aspects of MID (Rokers et al 2009). In our previous work, we emphasized that the V3A ROI responded strongly to a central disk alternating between disparities (Cottereau et al 2012b(Cottereau et al , 2012c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these connections were statistically significant for all the disparity pedestals and are therefore probably independent of the specific disparity values used in our experiment. Recent fMRI studies have demonstrated that both areas hMTϩ and V3A are highly responsive to various aspects of MID (Rokers et al 2009). In our previous work, we emphasized that the V3A ROI responded strongly to a central disk alternating between disparities (Cottereau et al 2012b(Cottereau et al , 2012c.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on their psychophysical studies, Cumming and Parker (1994) proposed that MID depended solely on the detection of changes in disparity over time (CDOT). Although these two models imply vastly different neural architectures (IOVD is based on motion-selective cells, while CDOT is based on disparity-selective cells), most current studies have shown that both IOVD and CDOT support the perception of MID (Nefs et al 2010;Rokers et al 2009). It should be noted that neither IOVD nor CDOT cues alone are sufficient for defining 3D motion trajectories in a general fashion (Lages and Heron 2010).…”
mentioning
confidence: 85%
“…The sensory memory for apparent rotation of SFM displays can be disrupted by TMS of cortical area hMT/V5 (Brascamp et al, 2010), which is known to play a prominent role in processing visual motion (Born & Bradley, 2005;Campana et al, 2002;Orban, 2011;Rokers, Cormack, & Huk, 2009;Tootell et al, 1995). In the context of binocular rivalry, a sensory memory for faces appears to engage the fusiform face area (FFA), as well as several fronto-parietal regions (Sterzer & Rees, 2008).…”
Section: Neural Substrates Of Sensory Memorymentioning
confidence: 99%
“…Since similar dichoptic stimuli presented to human observers in the same study resulted in the perception of coherent pattern motion despite the occurrence of binocular rivalry, the ability of dichoptic presentation to negate pattern responding in single neurons suggests that pattern sensitivity in some MT cells may operate monocularly. Furthermore, research on motion-indepth perception has provided evidence that 2-D plaid motion is extracted at a monocular locus prior to binocular recombination to form a 3-D percept (Rokers, Cormack, & Huk, 2009;Rokers, Czuba, Cormack, & Huk, 2011). This is supported by Guo, Benson, and Blakemore (2004), who found that a significant minority of V1 neurons responded to pattern rather than component motion.…”
Section: Discussionmentioning
confidence: 95%